Antiangiogenic therapy for primitive neuroectodermal tumor with thalidomide: A case report and review of literature. Issue 51 (December 2017) - Li, Qing; Liu, Yong; Yu, Yang
Abstract: Rationale: Peripheral primitive neuroectodermal tumor (PNET) is a kind of small round cell tumor derived from primitive neuroectodermal tumor. Patient concerns: PNET is a highly malignant tumor that is subordinated to Ewing sarcoma. It occurs predominantly in soft tissue and bone and rarely in the bronchi and lung. Traditional surgery, radiotherapy, and chemotherapy are used for the treatment of PNET, but are usually ineffective. Diagnoses: There was a rare case of a 17 year-old man diagnoses with primary pulmonary PNET. Interventions: The patient was treated by the remedy treatment with thalidomide after the poor effect of conventional radiotherapy and chemotherapy. Outcomes: The patient survived without disease progression for 15 months and was in stable condition. Lessons: Thalidomide provides a choice for maintenance therapy in PNET.